THE EFFECT OF SALINITY ON GROWTH AND NUTRIENT COMPOSITION IN BROAD BEAN (Vicia faba L.) SEEDLINGS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2010)
Broad bean-faba bean-(Vicia faba L.), one of the cultivated species of the family Fabaceae, is grown in large quantities in nearly every part of Turkey as an important source of animal and human food. Our objective was to determine the influence of two salinity levels (50 and 100 mM NaCl, named Si and S2, respectively) on the growth and nutrient composition in relatively salt-tolerant (or moderately sensitive) broad bean seedlings, grown in a greenhouse in pots containing perlite. The results indicated reductions in plant height, number of internodes and leaf dry weights of both cultivars (cv. Eresen 87, cv. Filiz 99) on exposure to salinity level and showed a significant response when exposed to S2 salinity level. According to the flame photometer (FP), flame atomic absorption spectrophotometers (FAAS) and inductively coupled plasma atomic emission spectrometry (ICP-AES) analyses of Filiz 99, Na+ was found in higher amounts in roots, stems and leaves of seedlings exposed to S2. In leaves, the elements K+, Ca2+ and Mg2+ were decreased significantly. In the leaves of cv. Filiz 99, sodium and potassium content was 3- and 2.4- times higher than in cv. Eresen 87. Cv. Filiz 99 was slightly more resistance to salinity that might be a good choice to grow where the soils affected by NaCl at moderate stress levels.
Keywords: Salinity; broad bean; Vicia faba L.; nutrients; DRY-MATTER YIELD; SALT-STRESS; SODIUM-CHLORIDE; MINERAL-COMPOSITION; NITROGEN-FIXATION; IONIC RELATIONS; WATER RELATIONS; SOIL-SALINITY; CALCIUM; PLANTS